Description and morphological phylogeny of Otorongo, a new Andean genus of long-legged flies (Diptera, Dolichopodidae) with claw-like leg spurs - Quevedo, Lucas; Soares, Matheus M. M.; Ramos-Pastrana, Yardany (Zootaxa, 2026)
Otorongo Quevedo, Soares & Ramos-Pastrana gen. nov. is erected to accommodate four remarkable newly described species from Colombia and Peru: Otorongo deinonychus sp. nov. (Colombia), O. piscator sp. nov. (Peru), O. runyoni sp. nov. (Colombia) and O. terrificus sp. nov. (Colombia). A cladistic analysis using a morphology-based matrix with 35 characters and 10 terminal taxa, comprising exemplars of most of the Sympycninae genera known from Neotropical fauna was performed to examine the relationships and monophyly of the newly proposed genus. We recovered Otorongo gen. nov. as a monophyletic group, with six autapomorphies mainly associated with male secondary sexual characters: (1) scutellum bearing a fringe of short, hair-like setae, (2) femur III arched, (3) femur III about 2 times wider than femur II, (4) posterodorsal apex of tibia III with a claw-like spur reaching the base of IIIt1, (5) IIIt1 with hook-like anterior bristle, and (6) presence of basal sclerite of sperm pump. The main diagnostic characters are discussed, as well as the relationship between Otorongo gen. nov. and other Sympycninae genera. An illustrated dichotomous key and a distribution map to species are also provided.